Islam and Literalism: Literal Meaning and Interpretation in Islamic Legal Theory By Robert Gleave (Edinburgh, UK: Edinburgh University Press, 2013. 212 pages.) (American Journal of Islam and Society, 2014)
This book surveys the development of literal meaning and literalism in Islamand Islamic legal theory (uṣūl al-fiqh) in particular. The term literal meaningrefers to the meaning that a text is believed to hold “in itself” by virtue of thesound-meaning relationships of words that were “coined” (waḍ‘) at some pointin time. Although Muslim debates on how words were coined (see secondchapter) are quite interesting and at times entertaining, the origin of languagewas secondary to the language’s actual existence. In other words, legal theoristscontended that the establishment of the “sound-meaning connection” wasmore important than who established it and when.Literalism, the other focus of the book, is the view that Islamic law privilegesliteral meaning. As Gleave explains in his first chapter, literalism seesliteral meaning as having an “advantage” over allusion, metaphor (majāz),and other kinds of meaning because it holds a “higher level of epistemologicalsecurity” (p. 1). Detecting the author’s intended meaning, although ideal, isfraught with uncertainties for it involves discerning another person’s intentions.In other words, for legal theorists, the literal can be established througha strict science of language and more importantly functions as a “startingpoint” for understanding texts which gives it a central role in hermeneutics.Even if the literal meaning is shown not to be the author’s intended meaning,it is nevertheless essential for controlling and understanding the linguistic andsemantic parameters of a word and the overall text in question.Gleave makes it clear that his purpose is not to establish whether or notthere is such a thing as literal meaning but instead to demonstrate the importanceof its various concepts and the role they played for Muslim legal theoristsof all sects as understanding how a language system works is key to grasping“God’s meaning when he addresses (khiṭāb) his servants” (p. 35). The firsttwo chapters are useful introductions to concepts of literal meaning in legaltheory. The third chapter, where the author traces one of the early conceptsand uses of literal meaning in Qur’anic exegesis, delineates its early historicalemergence in Islamic thought. This is significant for Islamic law and legaltheory as later Muslim legal hermeneutics had “imprints” of the debates thattook place in scriptural exegesis where literal meaning was often identified(e.g., through establishing what a word “literally” meant by tracing its ...